Bridging the divide between primary health care and community - Buys, Lüet Schraader (School of Architecture, Planning and Geomatics, 2017)
South African cities have a complex social and physical post-Apartheid layering. The historical legacy, referring here specifically to the inadequate roll-out of public facilities in areas and uprooting as well as separating of communities, have resulted in under serviced environments that can lack social cohesion and often struggle with poverty. Public institutions play a catalytic role within a community. To this end, health care portrays the government in a legible 'provider' role and is, in some ways, an obvious way to make citizens feel valued in comparison with other public institutions. Health care institutions impact the community in a unique way due to the combination of specificity of service and the emotive way it is experienced by the individual. This dissertation aims to research, define (and ultimately) test a strategy that aims to stitch together the fissure between community and institutions, by rethinking the urban interface of generic primary health care facilities. This research is structured around themes of theory, policy, the continuum of care and physical environments; each in order to better understand what and how the 'gap' between health care institution and community is constructed. Programmatic and/or spatial ideas that inform the architectural design. This dissertation asserts that providing 'traditional' generic institutions sustains rather than improves the life of the community. The research suggests that existing health care facilities can be more effective as public spaces by introducing new programmes, disaggregating the formal interface, redefining and activating a new urban threshold and providing meaningful open space. The design ultimately aims to act as a new skin or threshold through which institutions relate to the community.